2022
DOI: 10.1039/d2an00685e
|View full text |Cite
|
Sign up to set email alerts
|

Plastic-based lateral flow immunoassay device for electrochemical detection of NT-proBNP

Abstract: A low-cost plastic-based lateral flow device was developed to detect NT-proBNP, a heart failure marker, using the electrochemical metalloimmunoassay technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Lateral Flow Sensors [56,72] Uses capillary action to transport NT-proBNP to a detection zone, resulting in a visual signal.…”
Section: Biosensor Type Principle Of Detection Advantages Disadvantagesmentioning
confidence: 99%
“…Lateral Flow Sensors [56,72] Uses capillary action to transport NT-proBNP to a detection zone, resulting in a visual signal.…”
Section: Biosensor Type Principle Of Detection Advantages Disadvantagesmentioning
confidence: 99%
“…Then, the group developed several immunosensors, where a GE/ASV electrochemical method was utilized to detect different shapes of AgNP labels. 104,[115][116][117][118][119][120][121][122] It was demonstrated that the shape of the AgNP played a crucial role in determining the detection efficiency of metalloimmunoassay based on GE/ASV process. Specifically, it was shown that the LOD and analyte detection range could be tuned by simply altering the shape of the silver nanoparticle.…”
Section: Effect Of Agnp Shape and Size On The Ge Reactionmentioning
confidence: 99%
“…Recently, Raj et al developed a plastic-based lateral-flow device called oc Flow for carrying Ag-based metalloimmunoassay to detect NT-proBNP in human serum samples. 122 The oc Flow device was developed by patterning hydrophilic regions on open hydrophobic surfaces, allowing spontaneous sample flow via capillary and hydrodynamic forces. An electrochemical detection zone was defined downstream by screen-printed carbon paste electrodes with a small magnet underneath to concentrate immunoconjugate attached to magnetic microbeads.…”
Section: Microfluidic Flow Platforms For the Detection Of Agnp-based ...mentioning
confidence: 99%
“…Various efforts in developing NT-proBNP POC biosensors have been reported in the literature with many adopting the low cost lateral flow assay (LFA). However, the sensitivity, precision, and/or dynamic range of these LFAs have fallen short of clinical requirements, leaving a gap for a fully functional POC device. , Surface plasmon resonance (SPR) biosensors have also been implemented for the POC detection of NT-proBNP but have also fallen short of clinical sensitivity requirements, with limits of detection (LoD) only in the ng/mL range. , Another approach is the field effect transistor (FET) biosensor that Sinha et al developed as an integrated POC device for rapid and sensitive detection of NT-proBNP based on FET sensors with near-sufficient performance but an inability to measure whole blood . Sarangadharan et al reported a hand-held sensor using gravity sedimentation to separate plasma from blood by inverting the sensor after applying blood but showed unacceptable variation from sensor to sensor.…”
Section: Introductionmentioning
confidence: 99%